High-intensity kayak performance after adaptation to intermittent hypoxia - Bonetti, D. L.; Hopkins, W. G.; Kilding, A. E. (International Journal of Sports Physiology and Performance, 2006)
Live-high train-low altitude training produces worthwhile gains in performance for endurance athletes, but the benefi ts of adaptation to various forms of artifi cial altitude are less clear. Purpose: To quantify the effects of intermittent hypoxic exposure on kayak performance. Methods: In a crossover design with a 6-week washout, we randomized 10 subelite male sprint kayak paddlers to hypoxia or control groups for 3 weeks (5 days/week) of intermittent hypoxic exposure using a nitrogen-fi ltration device. Each day's exposure consisted of alternately breathing hypoxic and ambient air for 5 minutes each over 1 hour. Performance tests were an incremental step test to estimate peak power, maximal oxygen uptake, exercise economy, and lactate threshold; a 500-m time trial; and 5 × 100-m sprints. All tests were performed on a wind-braked kayak ergometer 7 and 3 days pretreatment and 3 and 10 days posttreatment. Hemoglobin concentration was measured at 1 day pretreatment, 5 and 10 days during treatment, and 3 days after treatment. Results: Relative to control, at 3 days posttreatment the hypoxia group showed the following increases: peak power 6.8% (90% confidence limits, ± 5.2%), mean repeat sprint power 8.3% (± 6.7%), and hemoglobin concentration 3.6% (± 3.2%). Changes in lactate threshold, mean 500-m power, maximal oxygen uptake, and exercise economy were unclear. Large effects for peak power and mean sprint speed were still present 10 days posthypoxia. Conclusion: These effects of intermittent hypoxic exposure should enhance performance in kayak racing. The effects might be mediated via changes in oxygen transport.